Kepastian Hukum vs Ketidakpastian Kerja: Substansi Ketenagakerjaan dalam Undang-Undang Nomor 6 Tahun 2023 tentang Cipta Kerja - Izzati, Nabiyla Risfa (Fakultas Hukum Universitas Islam Indonesia, 2024)
The enactment of Law Number 6 of 2023 on the Determination of Government Regulations in Lieu of Law Number 2 of 2022 (Perppu No. 2 of 2022) on Job Creation into Law (also known as Law No. 6 of 2023) has brought forward a number of pros and cons. The government argues that Perppu No. 2 of 2022, which was later amended into Law No. 6 of 2023, bears the urgency to be issued in order to guarantee legal certainty after Law Number 11 of 2020 on Job Creation was declared conditionally unconstitutional by the Constitutional Court. Meanwhile, the civil society movement and labor unions firmly reject Perppu No. 2 of 2022 and Law No. 6 of 2023. The labor union argues that the employment cluster in Law No. 6 of 2023 continues the problems as found in Law No. 11 of 2020 which led to the uncertainty of job. This article examines the basis of philosophical rationality and the validity of the arguments for legal certainty narrated by the Government, in the making of Perppu No. 2 of 2022 and Law No. 6 of 2023. This argument was then compared with the narratives and rationales for the uncertainty of job that were put forward by the labor unions, especially on the PKWT and outsourcing issues. The research was carried out in a normative juridical manner by examining the substance of Law No. 6 of 2023 and related laws and regulations. The results of this study indicate that in general, the employment cluster in Law No. 6 of 2023 does not bring legal certainty and actually perpetuates the uncertainty of job. Instead of providing legal certainty, the lack of synchronization with the implementing regulations of Law No. 11 of 2020 which remain in effect, as well as the emergence of additional articles related to wages, could actually provide additional legal uncertainty after the enactment of Law No. 6 of 2023.Keywords: Job Creation, Omnibus Law, Uncertainty of Job, Workers' Rights. AbstrakDiundangkannya Undang-Undang Nomor 6 Tahun 2023 tentang Penetapan Peraturan Pemerintah Pengganti Undang-Undang Nomor 2 Tahun 2022 tentang Cipta Kerja menjadi Undang-Undang (UU 6/2023) mengundang banyak pro dan kontra. Pemerintah berargumen bahwa Perppu 2/2022 yang selanjutnya disahkan menjadi UU 6/2023 mendesak untuk dikeluarkan untuk menjamin kepastian hukum pasca Undang-Undang Nomor 11 Tahun 2020 tentang Cipta Kerja dinyatakan inkonstitusional bersyarat oleh Mahkamah Konstitusi. Sedangkan, gerakan masyarakat sipil dan serikat buruh dengan tegas menolak Perppu 2/2022 maupun UU 6/2023. Serikat buruh berargumen bahwa kluster ketenagakerjaan dalam UU 6/2023 melanjutkan permasalahan UU 11/2020 yang membawa ketidakpastian kerja. Artikel ini menguji dasar rasionalitas filosofis dan kesahihan argumentasi kepastian hukum yang dinarasikan oleh Pemerintah, dalam pembuatan Perppu 2/2022 dan UU 6/2023. Argumentasi ini kemudian dibandingkan dengan narasi dan argumentasi ketidakpastian kerja yang digaungkan oleh serikat pekerja, utamanya dalam isu PKWT dan alih daya. Penelitian dilakukan secara yuridis normatif dengan mengkaji substansi dari UU 6/2023 dan peraturan perundang-undangan terkait. Hasil dari kajian ini menunjukkan bahwa secara umum, klaster ketenagakerjaan dalam UU 6/2023 tidak membawa kepastian hukum dan justru melanggengkan ketidakpastian kerja. Alih-alih memberikan kepastian hukum, ketidaksinkronan dengan peraturan pelaksana UU 11/2020 yang tetap berlaku, serta munculnya pasal tambahan terkait pengupahan, justru dapat memberikan ketidakpastian hukum tambahan pasca berlakunya UU 6/2023.Kata Kunci: Cipta Kerja, Hak Pekerja, Ketidakpastian Kerja, Omnibus Law.